POLICY STRATEGY FOR EMPOWERMENT OF BORDER AREA IN IMPROVING MARITIME SECURITY - Richard Martin; Kornia Adhi Nugraha; Wawan Kusdiana; Eko Krisdiono (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2022)
The border area of ​​a country is the main capital of a country's sovereignty. One of the islands whose position is at the forefront and at the same time the outermost border of Indonesia and other countries is Alfa Island. The research method used in this research is to use the integration of strength, weakness, opportunity, and threat (SWOT) analysis methods and the Borda method in formulating a strategy for developing the empowerment of the Miangas Island marine defence area. SWOT analysis is used to formulate and provide alternatives in the development strategy of developing a strategy for the empowerment of the Alfa Island marine defence area. And the Borda method is used to determine priorities for the selected strategy. With this research, it is hoped that it can encourage and become government input in managing the policies of the outermost islands by giving special attention to minimizing vulnerabilities and potential threats and increasing the positive potential that already exists on Alfa Island. Based on the research results, obtained 6 strategies. The weight calculation results show that the WO 1 strategy has the highest weight and is a priority strategy, which is to take advantage of the Indonesian Navy's MEF policy opportunities by increasing the Posal Alfa Capability that supports active patrols and sea operations of Posal Alfa. Keywords: SWOT Analysis, Alfa, Borda. Method